The financial impacts of lease capitalisation on an airline’s financial reporting: a case study of AirAsia Group Berhad / Sue Chern Ooi, Chee Chee Lim and Hooi-Laing Boo - Sue, Chern Ooi; Chee, Chee; Hooi-Laing, Boo (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Effective 1 January 2019, the International Accounting Standards Board (IASB) introduced IFRS 16 Leases to replace IAS 17 Leases. The aviation industry would be affected by the change in leases standard as IFRS 16 Leases will result in larger assets and liabilities being recorded in the balance sheet. In light of this, this study aimed to examine the financial impacts of lease capitalisation and IFRS 16 Leases on an airline through the constructive lease capitalisation method and financial ratio analysis. AirAsia Group Berhad (AirAsia) was selected because its aircraft are predominantly leased and it was predicted to be affected by IFRS 16 Leases. The financial data of AirAsia was analysed before and after the adoption of IFRS 16 Leases from 2017 to 2019. The results showed that the adoption of IFRS 16 Leases had led to an increase in the amount of AirAsia’s assets and liabilities and caused adverse changes in AirAsia’s D/E ratio, D/A ratio, ROE ratio and ROA ratio with the exception to its asset turnover ratio. This study contributes to literature and practice by addressing the concerns raised by the IASB on the impacts of lease capitalisation on financial reporting following the implementation of IFRS 16 Leases.